Low cost removal of disperse dyes from aqueous solution using palm ash - Isa, M.H.; Lee, S.L.; Asaari, F.A.H.; Aziz, H.A.; Ramli, N.A.; Dhas, J.P.A. (2007)
Palm oil and textile industries are important contributors to Malaysia’s economic growth. However, these industries also generate various pollutants of the environment. This research explores the possibility of using a low cost adsorbent i.e. ash produced from palm oil factory, for the removal of dyes from aqueous solution. For the treatment to be truly low cost, not only should the adsorbent be easily and cheaply available in abundance but it should also require minimal or no pre-treatment, for expensive pre-treatment procedures would add to the overall treatment cost. Two commercial dyes i.e. disperse blue and disperse red were used. The study incorporates both batch as well as continuous flow experiments. The effects of different system variables, viz., pH, initial dye concentration and agitation time were studied in the batch tests. Acidic pH was found to favour dye removal. The optimum pH and agitation time for the removal of the two dyes were 2 and 60 min, respectively. Both Langmuir and Freundlich isotherms could be used to describe the adsorption of the dyes, with the former yielding somewhat better fits. The experimental data fitted well to the pseudo-second-order kinetic model with R2 > 0.98 for all concentrations (50e250 mg/l) tested. Column plugging was the main problem encountered due to the fine particle size of the ash. Pelletisation of ash using calcium oxide and calcium sulphate was not successful. For industrial application, pelletisation will have cost implications and may not be recommended. Ash may be better used in its natural form in batch process.